Two new stygobiotic species of Elaphoidella (Crustacea: Copepoda: Harpacticoida) with comments on geographical distribution and ecology of harpacticoids from caves in Thailand - Watiroyram, Santi; Brancelj, Anton; Sanoamuang, La-Orsri (Zootaxa, 2015)
Elaphoidella thailandensis sp. nov. and E. jaesornensis sp. nov., collected during an investigation of cave-dwelling copepod fauna in the northern part of Thailand, are described and figured herein. The new species were collected from pools filled by percolating water from the unsaturated zone of a karstic aquifer in Phitsanulok and Lampang Provinces, respectively. Elaphoidella thailandensis, from Tham Khun cave, is distinguished from its congeners by the two-segmented endopod of pediger 1, the absence of endopod on pediger 4, and the setal formula 4, 5, 6 for the distal exopodal segment of pedigers 2–4. Elaphoidella jaesornensis, from Tham Phar Ngam cave, is distinguished from its most closely related species, E. namnaoensis Brancelj, Watiroyram & Sanoamuang, 2010, by the armature formula of the endopod of pedigers 2–5. The geographical distribution and ecology of Harpacticoida from Thai caves is also presented.